2020
DOI: 10.22460/project.v3i2.p161-167
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Augmented Reality (AR) In EFL Class For Teaching Vocabulary

Abstract: In the industrial era 4.0, the use of technology in the learning process is an important element. Teachers need to be more technologically in their teaching process since the use of technology has become a lifestyle. Augmented Reality (AR) is an interactive experience of a real-world environment which is considered effective as good medium in learning especially in English vocabulary. This article aims to explore the use of AR for young learners by comparing it with conventional paper flashcards. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…In terms of how AR is practiced in English language learning, the findings look into the level of learners involved in the studies, the location of AR implementation and either they are markerbased or markerless. The results of this study show that AR was mostly used in primary school with 40% of level of learners participated in English language learning by using this technological tool Yaacob, 2019;Solak & Cakir, 2016;Chen , 2018;Tobar-Munoz et.al., 2017;Danaei et.al., 2020;Sadikin & Martyani., 2020;Martinez et.al., 2017;). The level of learners participated in ELL using AR at the tertiary level and preschool show the same percentage of 50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of how AR is practiced in English language learning, the findings look into the level of learners involved in the studies, the location of AR implementation and either they are markerbased or markerless. The results of this study show that AR was mostly used in primary school with 40% of level of learners participated in English language learning by using this technological tool Yaacob, 2019;Solak & Cakir, 2016;Chen , 2018;Tobar-Munoz et.al., 2017;Danaei et.al., 2020;Sadikin & Martyani., 2020;Martinez et.al., 2017;). The level of learners participated in ELL using AR at the tertiary level and preschool show the same percentage of 50%.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, marker-based AR is mostly used indoor meanwhile, markerless AR is often used outdoor. Most of the studies carried out AR indoor Che Samihah et.al., 2019;Yaacob et.al., 2019;Solak & Cakir, 2016;Chen , 2018;Taskiran, 2018;Redondo et.al., 2019;Tobar-Munoz et.al., 2018;Danaei et.al., 2020;Sadikin & Martyani, 2020;Martinez et.al., 2017;Al-Asheeri, 2017;Safar et.al., 2017;Chen & Chan, 2019;Soo et.al., 2019;Tsai, 2020) compared to outdoor (Richardson et.al., 2016;Yeh & Tseng, 2020). At the same time, the studies also showed that AR can be used simultaneously indoor and outdoor (Lee et.al., 2019;Wang & Khambari, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students struggled to use terms accurately inside the post-assessment practice statement segment. Conversely, it has more of a broad consensus after conducting their AR post-assessment (Sadikin & Martyani, 2020). People had several "tip of the tongue" occasions in which they had been trying to recall context or components of a term but simply failed to get most of the facts through, plus students were very precisely recalling visuals or aspects of the AR environment throughout their exemplary phrases (Tsai, 2020).…”
Section: Binhomran and Altalhab 2021mentioning
confidence: 99%
“…The results show that AR could significantly improve the vocabulary learning (Solak & Cakir, 2016;Chen & Chan, 2019;Lee et al, 2019;Yaacob et.al. 2019;Sadikin & Martyani, 2020;Tsai, 2020). This is also supported by Cheng (2020) in which "AR has a significant effect on students' English vocabulary learning with various levels of low, intermediate and high groups" (p. 170).…”
Section: Vocabulary Learningmentioning
confidence: 99%